Uji Efektivitas Beberapa Teknik Ekstraksi dan Dry Heat Treatment terhadap Viabilitas Benih Tomat (Lycopersicum esculentum Mill.) - GUNARTA, I WAYAN; RAKA, I GUSTI NGURAH; ASTININGSIH, A.A.M. (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2014)
ABSTRACT Efectivity Test for Some Extraction Techniques and Dry Heat Treatment on Tomato Seed ( Lycopersicum esculentum Mill.) This experiment aimed to obtain the most effective extraction method and determine the effect of dry heat treatment to produce high quality tomato seeds. The design used was completely randomized design with 3 treatments and 9 replications. The treatments include: (1) Bl : fresh tomato seeds taken, immediately dried to 5% moisture content, (2) Ba: fresh tomato seeds taken, then soaked in water for 24 hours, dried to 5% moisture content, (3 ) Bh: fresh tomato seeds taken, then soaked in a solution of 2% HCl for 2 hours, then dried until the moisture content of 5%. Seeds obtained from each extraction technique is divided into two lots, one lot for Dry Heat Treatment (DHT) and the other one lot for Non Dry Heat Treatment (NDHT). The variables measured were the number of seed moisture content of 5% by weight of unity, purity of the seeds, the total viability, potential viability, vigor speed germination, and seedling growth vigor. The results showed the significant diference between extraction treatment to all of variables tested, while the granting of DHT on the seed does not provide a response to tomato seed quality, on all variables tested. Bh extraction treatment showed the best results with the highest values  on all of variables tested.   Key word : tomato seeds , extraction, dry heat treatment, viability and vigor .